2017
DOI: 10.1093/ntr/ntx273
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Potential Harm: Summary of an FDA-Sponsored Public Workshop

Abstract: This paper synthesizes the main findings from the 2016 FDA-sponsored workshop focused on biomarkers of potential harm (BOPH) and highlights research areas that could further strengthen the science around BOPH and their applicability to tobacco regulatory science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 76 publications
0
55
0
Order By: Relevance
“…The present research on IEGs after acute WP exposure is the first of its kind and addresses the need for genetic biomarkers that are specifically tailored to WP use 139. We adopted previous approaches to show that IEGs may potentially quantify and predict harmful effects in humans, known as biomarkers of potential harm, based on the magnitude and direction of expression 140–142. Furthermore, IEG testing in the nasal epithelium and gingiva (the gums) is a promising and non-invasive alternative with clinical relevance 143 144.…”
Section: Discussionmentioning
confidence: 99%
“…The present research on IEGs after acute WP exposure is the first of its kind and addresses the need for genetic biomarkers that are specifically tailored to WP use 139. We adopted previous approaches to show that IEGs may potentially quantify and predict harmful effects in humans, known as biomarkers of potential harm, based on the magnitude and direction of expression 140–142. Furthermore, IEG testing in the nasal epithelium and gingiva (the gums) is a promising and non-invasive alternative with clinical relevance 143 144.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 2] The urinary metabolites “prostaglandin E 2 metabolite” (PGE-M) and ( Z )-7-[1 R ,2 R ,3 R ,5 S )-3,5-dihydroxy-2-[( E ,3 S )-3-hydroxyoct-1-enyl]cyclopentyl]hept-5-enoic acid (8- iso -PGF 2α ) are accepted biomarkers of inflammation and oxidative damage, respectively, and are part of a group of measures that have been termed “biomarkers of potential harm”. [36] Fig 1.…”
Section: Introductionmentioning
confidence: 99%
“…These decreases in biomarker levels are far less than observed for typical biomarkers of exposure, which decrease by 39–92% within only 3 days after smoking cessation [34]. While biomarkers of exposure depend mainly on specific toxicant exposures which stop upon smoking cessation, biomarkers such as 8- iso -PGF 2α and PGE-M, which have been termed “biomarkers of potential harm” [4], result from alterations in physiologic processes related to oxidative damage and inflammation [35, 36]. PGE-M has also been described as a potential cancer biomarker and its levels have been positively associated with high saturated fat intake, obesity, and poor self-reported health status in addition to cigarette smoking and other factors [37].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent nested case-control study within the prospective Shanghai Cohort Study demonstrated a significant relationship of 8- iso -PGF 2α to lung cancer incidence in cigarette smokers [3]. Thus, 8- iso -PGF 2α and PGE-M are considered “biomarkers of potential harm” reflecting early biological effects strongly associated with disease [4].…”
Section: Introductionmentioning
confidence: 99%